2020
DOI: 10.1111/jns.12413
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin‐ and docetaxel‐induced polyneuropathy: clinical and neurophysiological characteristics

Abstract: The aim of this study was to evaluate the presence and characterization of chemotherapyinduced neuropathy (CIPN) and neuropathic pain 5 years after adjuvant chemotherapy with docetaxel or oxaliplatin. Patients from an ongoing prospective study, who had received adjuvant chemotherapy with docetaxel or oxaliplatin in 2011 to 2012 were invited to participate. The patients underwent a thorough examination with interview, neurological examination, questionnaires, assessment tools, nerve conduction studies (NCS), qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 56 publications
(125 reference statements)
3
33
0
Order By: Relevance
“… 52 However, the evidence for small fiber involvement with paclitaxel treatment is more convincing, as shown by reduction in both intraepidermal and corneal nerve fiber densities. 53 , 54 Motor nerves are usually only minimally involved in CIPN as found by Bennedsgaard and colleagues, 14 which is also reflected in the current study. Large sensory nerve fiber function in nerve conduction studies have been shown to be reduced with CIPN.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“… 52 However, the evidence for small fiber involvement with paclitaxel treatment is more convincing, as shown by reduction in both intraepidermal and corneal nerve fiber densities. 53 , 54 Motor nerves are usually only minimally involved in CIPN as found by Bennedsgaard and colleagues, 14 which is also reflected in the current study. Large sensory nerve fiber function in nerve conduction studies have been shown to be reduced with CIPN.…”
Section: Discussionsupporting
confidence: 87%
“…Large sensory nerve fiber function in nerve conduction studies have been shown to be reduced with CIPN. 14 However, a cutoff value for sensory nerve conduction amplitudes for diagnosing CIPN is currently absent, with clinicians and researchers instead proposing a multimodal approach incorporating symptomatology as well as large and small nerve fiber assessments. 8 , 14 Future investigation of the ability of sensory nerve conduction studies and in vivo corneal confocal microscopy in differentiating patients with and without peripheral neuropathy during development and progression of the condition in longitudinal studies is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If sensory symptoms are limited to hands, median entrapment neuropathy should be also rule out. Long-term follow up of patients after oxaliplatin showed persistent low amplitudes at sensory nerves 3 year after treatment [38].…”
Section: Nerve Conduction Studies (Ncs)mentioning
confidence: 95%
“…The cornea is the most densely innervated region of the body, about 300–600 times that of the skin 15 , contributing to its sensitivity to a range of stimuli. While research has shown an association between ocular surface dysfunction and sub-basal corneal nerve damage in neuropathic conditions, particularly diabetic peripheral neuropathy 16 18 , evidence is minimal for chemotherapy-induced peripheral neuropathy 19 , 20 . In-vivo corneal confocal microscopy has been proposed as a useful clinical and research instrument for detecting small nerve fiber changes of the corneal sub-basal nerve plexus in ocular diseases particularly dry eye disease 21 , as well as in the context of diabetic peripheral neuropathy 22 , 23 with emerging evidence with neurotoxic chemotherapy from both human and animal studies 19 , 24 .…”
Section: Introductionmentioning
confidence: 99%